2017
DOI: 10.2217/imt-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Prediction and Experimental Validation of a PE38-Based Recombinant Immunotoxin Targeting the Fn14 Receptor in Cancer Cells

Abstract: Coupled with bioinformatics, experimental approaches revealed that PE38-P4A8 could be used as a promising therapeutic agent for cancer cells expressing Fn14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Tertiary structure of the fusion protein by C-score -3.36 contained the highest C-score. In this study, ASGGPE and (G4S)3 linkers were used to isolate different segments (37). In another study, we designed and analyzed TGFαL3-SEB fusion protein that were optimized by CAI index 0.85 and by GC content 44.06% the overall stability of mRNA increased.…”
mentioning
confidence: 99%
“…Tertiary structure of the fusion protein by C-score -3.36 contained the highest C-score. In this study, ASGGPE and (G4S)3 linkers were used to isolate different segments (37). In another study, we designed and analyzed TGFαL3-SEB fusion protein that were optimized by CAI index 0.85 and by GC content 44.06% the overall stability of mRNA increased.…”
mentioning
confidence: 99%
“…They declared that this recombinant mut 1 IT (with IC50 5.o3 and 0.2 pM for ch-hep-3 and ch-hep-1, respectively) specifically killed tumor cells in mice, with a weak induction of VLS. Moreover, using the KDEL motif instead of EDLK in this immunotoxin probably has been affective in its high cytotoxicity, as shown in our previous studies on PE38 with [92,93] or without [94] KDEL motif-based immunotoxin. The authors suggested that mut 1 could be presented as a novel and effective candidate of PE-based immunotoxin for use against SM5-1 binding positive cells such as HCC cells.…”
Section: Anti-hcc Immunotoxinsmentioning
confidence: 71%
“…The highest C-score of -3.36 observed in tertiary structure of the fusion protein. For isolating two parts of the proteins, the ASGGPE and (G4S) 3 linkers were recruited (45).…”
Section: Discussionmentioning
confidence: 99%